Comparison of immunogenicity and safety of four doses and four double doses vs. standard doses of hepatitis B vaccination in HIV-infected adults: A randomized, controlled trial - Kanokporn Chaiklang (2018)
Background: HBV vaccination is recommended in HIV-infected adults with CD4+ cell count >200/mm3 although the efficacy is only 33.3% -65%. We conducted a randomized, controlled trial to evaluate the efficacy and safety of three regimens of HBV vaccination at Chiang Mai University Hospital, Thailand. Methods: From February 4, 2011 to May 4, 2012, 132 HIV-infected adults with CD4+ cell counts >200 cells/mm3, undetectable plasma HIV-1 RNA, and negative for all HBV markers were randomly assigned to receive one of three recombinant vaccine (Hepavax-Gene® Berna, Korea) regimens: 20 μg IM at months 0, 1, and 6 (Standard doses group, n=44), 20 μg IM at months 0, 1, 2, 6 (four doses group, n=44), or 40 ìg IM at months 0, 1, 2, and 6 (four double doses group, n=44). The primary outcomes were to compare the immunogenicity and safety between the four-doses groups with the Standard doses group. Results: At months 7 and 12, the percentages of responders (anti-HBs ≥10 mIU/mL) were 88.6% and 70.4% in the Standard doses group, 93.2% and 86.4% in the four doses group, (P=0.713 and 0.119), and 95.4% and 88.6% in the four double doses group, (P=0.434 and 0.062), respectively. Factors associated with a high titer level (anti-HBs ≥100 mIU/mL) were vaccination schedule and younger age. The most common adverse event was pain at the injection site (42.4%); this was significantly more frequent in the four double doses group compared to the Standard doses group. No serious adverse events were observed. Conclusions: In Northern Thailand, the standard three-doses HBV vaccination in HIV-infected adults with CD4+ cell counts >200 cells/mm3 and undetectable plasma HIV-1 RNA is highly effective. Although regimens of four injections of either standard or double doses could not significantly increase the response rate, these regimens may induce higher levels of antibody to the virus. Trial registration information: ClinicalTrials.gov; NCT1289106 © 2013 Chaiklang et al.